Retinal Thickness Changes Over Time in a Murine AD Model APPNL-F/NL-F - Salobrar-García, Elena; López-Cuenca, Inés; Sánchez-Puebla, Lídia; de Hoz, Rosa; Fernández-Albarral, José A.; Ramírez, Ana I.; Bravo-Ferrer, Isabel; Medina, Violeta; Moro, María A.; Saido, Takaomi C.; Saito, Takashi; Salazar, Juan J.; et al. (Frontiers in Aging Neuroscience, 2021)
Background: Alzheimer’s disease (AD) may presents retinal changes before brain pathology, suggesting the retina as an accessible biomarker of AD. The present work is a diachronic study using spectral domain optical coherence tomography (SD-OCT) to determine the total retinal thickness and retinal nerve fiber layer (RNFL) thickness in an APPNL-F/NL-F mouse model of AD at 6, 9, 12, 15, 17, and 20 months old compared to wild type (WT) animals. Methods: Total retinal thickness and RNFL thickness were determined. The mean total retinal thickness was analysed following the Early Treatment Diabetic Retinopathy Study sectors. RNFL was measured in six sectors of axonal ring scans around the optic nerve. Results: In the APPNL-F/NL-F group compared to WT animals, the total retinal thickness changes observed were the following: i) At 6-months-old, a significant thinning in the outer temporal sector was observed; ii) at 15-months-old a significant thinning in the inner temporal and in the inner and outer inferior retinal sectors was noticed; iii) at 17-months-old, a significant thickening in the inferior and nasal sectors was found in both inner and outer rings; and iv) at 20-months-old, a significant thinning in the inner ring of nasal, temporal and inferior retina and in the outer ring of superior and temporal retina was seen. In RNFL thickness, there was significant thinning in the global analysis and in nasal and inner-temporal sectors at 6 months old. Thinning was also found in the supero-temporal and nasal sectors and global value at 20 months old. Conclusions: In the APPNL-F/NL-F AD model, the retinal thickness showed thinning, possibly produced by neurodegeneration alternating with thickening caused by deposits and neuroinflammation in some areas of the retina. These changes over time are similar to those observed in the human retina and could be a biomarker for AD. The APPNL-F/NL-F AD model may help us better understand the different retinal changes during the progression of AD.